RESERVATION SYSTEM BOARD ADVERTISING ON BUS PT IKRA SANDALWOOD SHELTER LATITUDE USING VISUAL BASIC 6.0 - M. Fadjrin Gumilar; Rahayu Noveandini, SKom, MM (Jurnal Sistem Informasi, 2005)
Outdoor Advertising (outdoor advertising) can be seen around the city, either in the form of billboards or ads that are placed on the body of the bus. Unwittingly, the ads become one of the sights that decorate the city. This research aims at describing the ordering system, especially that there are billboards on bus stops / bus shelters on the "PT IKRA sandalwood latitude", an advertising company that provides media production services Outer Space Ads numbers located in Tebet, South Jakarta.